PENGARUH KEPERCAYAAN, KEMUDAHAN DAN HARGA TERHADAP MINAT BELANJA ONLINE - Dedi Susanto (LPPM STIE PERTIBA Pangkalpinang, 2022)
Nowadays online shopping is no longer a necessity but has become a lifestyle. Especially during the COVID-19 pandemic, with limited mobility so many transactions must be done online. This study aims to determine the effect of trust, convenience, and price on online shopping interest. This study involved 50 respondents involving Alumni of Bina Nusantara University majoring in accounting computerization class of 1997, with data collection methods using questionnaires and data analysis with multiple regression models. The results showed that the variables of trust, convenience, and the price had an effect on online shopping interest.